2020
DOI: 10.3324/haematol.2019.236125
|View full text |Cite
|
Sign up to set email alerts
|

BMP signaling is required for postnatal murine hematopoietic stem cell self-renewal

Abstract: Life-long production of blood from hematopoietic stem cells (HSC) is a process of strict modulation. Intrinsic and extrinsic signals govern fate options like self-renewal – a cardinal feature of HSC. Bone morphogenetic proteins (BMP) have an established role in embryonic hematopoiesis, but less is known about its functions in adulthood. Previously, SMAD-mediated BMP signaling has been proven dispensable for HSC. However, the BMP type-II receptor (BMPR-II) is highly expressed in HSC, leaving the possibility tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In particular, several key pathways essential for HSC function were enriched in the BM, including the RHO GTPase cycle signaling, AKT signaling, WNT signaling, BMP pathway, Runx1 pathway, and Notch signaling pathway. 17–20 Regarding PB HSCs, these regions exhibited enrichment in HS-GAG degradation and cell differentiation ( Fig. 5D ).…”
Section: Resultsmentioning
confidence: 96%
“…In particular, several key pathways essential for HSC function were enriched in the BM, including the RHO GTPase cycle signaling, AKT signaling, WNT signaling, BMP pathway, Runx1 pathway, and Notch signaling pathway. 17–20 Regarding PB HSCs, these regions exhibited enrichment in HS-GAG degradation and cell differentiation ( Fig. 5D ).…”
Section: Resultsmentioning
confidence: 96%
“…Elevated levels of VEGF stimulate angiogenesis and subsequent disease progression. morphogenic protein receptor 2 (BMPR-2) reduces the reconstitutive capacity of long-term repopulating HSCs following transplantation with BmprII À/À bone marrow cells suggesting an important role of BmprII in HSC self-renewal (Singbrant et al, 2010;Warsi et al, 2021). The bone marrow micro-environment has also been shown to influence HSC heterogeneity based on location within cellular networks.…”
Section: Adult Bone Marrow (Bm) Niche Micro-environmentmentioning
confidence: 99%
“…Whilst the role of the BMP/SMAD (small mothers against decapentaplegic)‐dependant pathway, like other self‐renewal pathways, is well understood in embryonic development, the effect of the canonical pathway in adult and foetal liver haematopoiesis seems dispensable in favour of alternative pathways. Recent work in xenograft mice has however suggested that a deficiency in bone morphogenic protein receptor 2 (BMPR‐2) reduces the reconstitutive capacity of long‐term repopulating HSCs following transplantation with BmprII −/− bone marrow cells suggesting an important role of BmprII in HSC self‐renewal (Singbrant et al, 2010; Warsi et al, 2021). The bone marrow micro‐environment has also been shown to influence HSC heterogeneity based on location within cellular networks.…”
Section: Adult Bone Marrow (Bm) Niche Micro‐environmentmentioning
confidence: 99%